Vachana Literature: Resistance Through a Unique Genre (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Literature, as an art form, is affected not only by external determinants but by dynamism within art itself that promotes or impedes change. -Rene WellekThe history of mankind is replete with resistances to various societal norms especially when the social milieu impinges the liberty of its people, creates a suffocating atmosphere even to lead normal life. However the newer governances after a passage of time turn out to be another government with newer weaknesses leading to another kind of governance. It is a vicious circle with no eternal solution. During such critical times literature has shown the way out of it, sometimes through its revolutionary concepts and at other times through healthy practices for the well-being of its people.Literature is a mirror of prevailing society. Through literature, one can discern the resistance to the unhealthy/unfair previous societies owing to its rigid practices, atrocities on subaltern communities, hegegmony of certain communities. During the 12th century Karnataka the Vachana literature endeavoured in all possible ways to sensitize the people about various blind and unfair practices of the previous epochs: caste system, superstitious beliefs, materialism, and denial of lower caste people to places of worship, belittling women, belief in Karma theory (or fatalism) and the like. The paper explores the resistances through Vachana literature, a unique literature which meant ‘promise’ or a ‘word’. Saint Akkmahadevi’ perspectives, who was known for the confluence of Bhatki, intense devotion, Jnana, spiritual knowledge and Vairagya, renunciation are emphasized. Vachanas related to attainment of spiritual knowledge would be discussed in Anubhava Mantapa, a religious academy, verified and documented to propagate its precepts to make the society rational and healthy. The Vachana literature is an offshoot of Bhakti Movement which spread across India with certain variations and the unique genres:Vachanas(Karnataka), abhangas(Maharashtra), Tevaram(Tamilnadu), ‘Sataka’(Andhra Pradesh). Society across India had the conviction that unless the priests mediate between the devotees and the Almighty one will not be bestowed with His blessings. However, the proponents of Bhakti Movement in general and Vachana Movement in particular through their resistance literature preached the laity to practise universal brotherhood which would ensure the eradication of various evil practices and spread universal brotherhood: inequalities between castes, materialism, denial of entry to lower caste people to temples and the like. The following Vachanas exemplifies the practice of universal brotherhood